EFFECT OF PLANTING PERIOD AND STANDARDS ON YIELD ELEMENTS AND WEIGHT OF 1000 GRAINS OF CROTALARIA (American Journal of Pedagogical and Educational Research, 2023)
This article describes the importance of crotalaria (Crotalaria juncea), a non-traditional leguminous crop cultivated in the alluvial soils of the Khorezm region, in the northern region of the republic, as well as the impact of the planting period and norms on the yield elements of the plant and the weight of 1000 grains, in agriculture. That is, the optimal planting period (20-25.04) and rate (10 kg/ha) for the production of more fruits, flowers and pods in one bush of crotalaria have been scientifically explained.